Redistribución de planta y programación de la producción: un enfoque integrado (2015)
The main concern of companies when they are going to implement a re-layout project is the disruption of manufacturing operations while the departments are moving. This paper presents an optimization model to make the project scheduling and the production planning in order to ensure the compliance of the demand during the re-layout project. For this purpose, we propose a mixed integer linear programming (MIP) that minimizes the costs of moving the departments, guarantees compliance of the demand and limits the duration of the project to a maximum. Our results show that when the average utilization of the machinery of the plant is greater than 60%, the re-layout project and the production planning are interdependent; therefore it is necessary to use an integrated approach as is proposed in this paper.